A Series of Novel Alleles of Ehd2 Modulating Heading and Salt Tolerance in Rice - Peng Xu; Shulei Hao; Xiaoxia Wen; Guifang Ma; Qinqin Yang; Ling Liu; Galal Bakr Anis; Yingxin Zhang; Lianping Sun; Xihong Shen; Qunen Liu; Daibo Chen; et al. (Plants)
Rice (Oryza sativa L.) is a staple crop for nearly half of the global population and one of China’s most extensively cultivated cereals. Heading date, a critical agronomic trait, determines the regional and seasonal adaptability of rice varieties. In this study, a series of mutants (elh5 to elh12) exhibiting extremely late heading under both long-day (LD) and short-day (SD) conditions were identified from an ethyl methanesulfonate (EMS) mutant library. Using MutMap and map-based cloning, the causative gene was identified as a novel allele of Ehd2/OsID1/RID1/Ghd10. Functional validation through CRISPR/Cas9 knockout and complementation assays confirmed its role in regulating heading. The elh6 mutation was found to cause intron retention due to alternative splicing. Ehd2 encodes a Cys-2/His-2-type zinc finger transcription factor with an IDD domain and transcriptional activity in yeast. Its expression peaks in developing leaves before heading and spikes during reproductive conversion. In elh6 mutants, delayed heading resulted from downregulating the Ehd1-Hd3a pathway genes. Salinity stress significantly hampers rice growth and productivity. Transcriptomic analysis of elh10 and ZH8015 seedlings exposed to salt stress for 24 h identified 5150 differentially expressed genes (DEGs) at the seedling stage, predominantly linked to stress response pathways. Ehd2 was revealed as a modulator of salt tolerance, likely through the regulation of ion transport, enzyme activity, and antioxidant systems. This study establishes Ehd2 as a pivotal factor in promoting heading while negatively regulating salt tolerance in rice.